2023
DOI: 10.1177/00222194231195624
|View full text |Cite
|
Sign up to set email alerts
|

Extended Time Accommodation and the Academic, Behavioral, and Psychological Outcomes of Students With Learning Disabilities

Xin Wei,
Susu Zhang

Abstract: This study analyzed performance, process, and survey data of eighth graders with learning disabilities (LDs) who took the 2017 National Assessment of Educational Progress (NAEP) digital math test. Compared with students with LDs who did not receive extended time accommodations (ETAs), students with LDs who received and used ETA scored significantly higher on the test, whereas students with LDs who received but did not use ETA scored significantly lower on the test. In addition, students with LDs in the two ETA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Furthermore, few studies have explored whether receiving other accommodations, including extended time accommodation (ETA), mitigates the impact of TTS. Notably, Wei and Zhang (2023) observed that students with learning disabilities who were granted ETA tended to use TTS more frequently. Similarly, Knoop-van Campen et al (2022) discovered that TTS usage extended reading time for both students with and without dyslexia.…”
Section: Limitations Of Previous Studiesmentioning
confidence: 97%
“…Furthermore, few studies have explored whether receiving other accommodations, including extended time accommodation (ETA), mitigates the impact of TTS. Notably, Wei and Zhang (2023) observed that students with learning disabilities who were granted ETA tended to use TTS more frequently. Similarly, Knoop-van Campen et al (2022) discovered that TTS usage extended reading time for both students with and without dyslexia.…”
Section: Limitations Of Previous Studiesmentioning
confidence: 97%